Microstructure and Mechanical Properties of Ti-35Nb-2Ta-3Zr Alloy by Laser Quenching - Zhang, Ting; Fan, Qing; Ma, Xiaoli; Wang, Wen; Wang, Kuaishe; Shen, Pingquan; Yang, Junlin (Frontiers in Materials, 2019)
In this work, using laser quenching technology to modify the surface of β-Ti-35Nb-2Ta-3Zr alloy. The microstructure and deformation mechanism of laser-quenched region were analyzed in detail by using X-ray diffraction (XRD), scanning electron microscope (SEM) and transmission electron microscope (TEM). Dislocations and α″ martensite transformation occur during the process. The cyclic loading-unloading stress-strain curve is used to evaluate the superelasticity of the alloy. After laser quenching, the superelasticity and microhardness of the alloy increases, and the toughness decreases. Grain coarsening is also obtained during laser quenching.